Turn a blind eye - Archer, Jeffrey, 1940- (Archer, Jeffrey, 1940- William Warwick novels, 2021)
"William Warwick, now a Detective Inspector, is tasked with a dangerous new line of work, to go undercover and expose crime of another kind: corruption at the heart of the Metropolitan Police Force. His team is focused on following Detective Jerry Summers, a young officer whose lifestyle appears to exceed his income. But as a personal relationship develops with a member of William's team, it threatens to compromise the whole investigation. Meanwhile, a notorious drug baron goes on trial, with the prosecution case led by William's father and sister. And William's wife Beth, now a mother to twins, renews an old acquaintance who appears to have turned over a new leaf, or has she? As the undercover officers start to draw the threads together, William realizes that the corruption may go deeper still, and more of his colleagues than he first thought might be willing to turn a blind eye."--Publisher.